Selection of energy source and evolutionary stable strategies for power plants under financial intervention of government - Ashkan Hafezalkotob; Reza Mahmoudi (Journal of Industrial Engineering International, 2017)
Currently, many socially responsible governments adopt economic incentives and deterrents to manage environmental impacts of electricity suppliers. Considering the Stackelberg leadership of the government, the government's role in the competition of power plants in an electricity market is investigated. A one-population evolutionary game model of power plants is developed to study how their production strategy depends on tariffs levied by the government. We establish that a unique evolutionary stable strategy (ESS) for the population exists. Numerical examples demonstrate that revenue maximization and environment protection policies of the government significantly affect the production ESS of competitive power plants. The results reveal that the government can introduce a green energy source as an ESS of the competitive power plants by imposing appropriate tariffs.
Keywords: 650; Evolutionary game theory; Green electricity; Power plant; Government intervention; Energy source selection